CD43 sialoglycoprotein modulates cardiac inflammation and murine susceptibility to Trypanosoma cruzi infection - Frederico Alisson-Silva; Natália Rodrigues Mantuano; Ana Luiza Lopes; Andréia Vasconcelos-dos-Santos; André Macedo Vale; Miriam Maria Costa; Judy L. Cannon; Ana Carolina Oliveira; Adriane R. Todeschini (Scientific Reports, 2019)
Abstract CD43 (leukosialin) is a large sialoglycoprotein abundantly expressed on the surface of most cells from the hematopoietic lineage. CD43 is directly involved in the contact between cells participating in a series of events such as signaling, adherence and host parasite interactions. In this study we examined the role of CD43 in the immune response against Trypanosoma cruzi, the protozoan parasite that causes Chagas’ disease, a potential life-threatening illness endemic in 21 Latin American countries according to the WHO. The acute stage of infection is marked by intense parasitemia and cardiac tissue parasitism, resulting in the recruitment of inflammatory cells and acute damage to the heart tissue. We show here that CD43 −/− mice were more resistant to infection due to increased cytotoxicity of antigen specific CD8+ T cells and reduced inflammatory infiltration in the cardiac tissue, both contributing to lower cardiomyocyte damage. In addition, we demonstrate that the induction of acute myocarditis involves the engagement of CD43 cytoplasmic tripeptide sequence KRR to ezrin-radixin-moiesin cytoskeletal proteins. Together, our results show the participation of CD43 in different events involved in the pathogenesis of T. cruzi infection, contributing to a better overall understanding of the mechanisms underlying the pathogenesis of acute chagasic cardiomyopathy.